Pengaruh Produk, Promosi, Penetapan Harga Dan Distribusi Terhadap Keputusan Pembelian Produk Kopi Bubuk Cap Kopi Kita Di Purbolinggo Lampung Timur - Imantoro, Jati; Rahayu, Sri Retnaning; Putriana, Nila (Jurnal Manajemen DIVERSIFIKASI, 2023)
Affordable prices, causing a lack of interest in buying our coffee stamped coffee products. Our coffee stamped coffee SME's have not been able to distribute their products optimally. The research design carried out in this study was quantitative research. Quantitative research is a research method based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical, with the aim of testing predetermined hypotheses. The results show that the product has a positive and significant effect. on the purchase decision of our coffee stamp powder coffee product. This shows that if the product increases, the purchasing decision also increases. The results show that promotion has a positive and significant effect on purchasing decisions for our coffee powder coffee products. This shows that if the promotion increases, the purchase decision also increases. Our coffee MSMEs are expected to be able to further increase product variables so that consumers are more confident in their purchasing decisions for our coffee stamped coffee products